KEADAAN SOSIAL EKONOMI RUMAHTANGGA MIGRAN PEREMPUAN DI DESA MISKIN WILAYAH BALI TIMUR - Sri Astiti, Ni Wayan (Jurnal Studi Jender SRIKANDI, 2012)
Female migrants from the research location – a poor village in the regency ofKarangasem – do not come from landless households (average hausehold property is0,75 ha) and their families live in a (semi) permanent house. The main push factor thatmakes women migrate is the infertility of the dry soil and the lack of job opportunitiesoutside the agricultural sector. The womwn primarily migrate to Gianyar, Denpasar andeven as far as Surabaya to increase their income (57,5%) or household welare (25%).Consequently the largest part of household income comes from economic activityoutside agriculture (78,9%). The womwn to go the city either because encouraged to doso by relativesm friends, or a broker, and a few go on their own initiative.